THE EFFECT OF FINANCIAL LITERACY, RISK PERCEPTION, RETURN PERCEPTION AND SOCIAL MEDIA INFLUENCERS ON THE INVESTMENT INTEREST OF THE MILLENNIAL GENERATION IN TEMANGGUNG REGENCY IN 2024 - Lestari, Wahyu; Albertus, Redy Herinanto; Murdo, Ilham Tri (Strategic Management Business Journal, 2025)
Research background: This study aims to examine the influence of financial literacy, risk perception, return perception, and social media influencers. The object of this research is the millennial generation in Temanggung Regency. Purpose of the article: This study indicate that perceived return and social media influencers have a positive effect on millennial generation investment interest in Temanggung Regency. Financial literacy and risk perception do not have a positive effect on millennial generation investment interest in Temanggung Regency. Methods: The data analysis technique used in this research is Multiple Linear Regression Analysis. Sampling in this study used cluster sampling technique. Respondent data collection used a questionnaire with a total of thirty-five statements and 111 participants. Each statement is measured with five Likert scales.